Determinants of Induction of Increased Synthesis of Plasminogen Activator Inhibitor Type-1 in Human Endothelial Cells by t-PA - Fujii, Satoshi; Sobel, Burton E (Thrombosis and Haemostasis, 1992)
Tissue-type plasminogen activator (t-PA) induces synthesis of a rapidly acting inhibitor, plasminogen activator inhibitor type-1 (PAI-1) in human umbilical vein endothelial cells (HUVEC) in culture. In vivo, an analogous process may induce negative feedback on the fibrinolytic system. To define specific determinants in the t-PA molecule contributing to the induction, PAI-1 synthesis was characterized in 35S-methionine labeled HUVEC in response to several molecular variants of t-PA. Catalytically active variants devoid of several specific structural domains in the A-chain retained the capacity to form complexes with PAI-1 and to induce increased concentrations of total PAI-1 (free and complexed) in conditioned media without depleting PAI-1 from the extracellular matrix. Surprisingly, a mutant t-PA with markedly reduced catalytic activity reflecting replacement of the active site serine with threonine (S478T) formed complexes with PAI-1 and induced increased PAI-1 synthesis as well. However, in contrast to wild-type t-PA and A-chain variants, it did not release 35S-methionine labeled PAI-1 from the extracellular matrix. Thus, its effects appeared to reflect increased secretion exclusively. Our results suggest that induction of PAI-1 synthesis in HUVEC by t-PA depends on its protease domain but that an active site serine is not a requirement.